2017
DOI: 10.11648/j.plant.20170506.14
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Atmospheric Humidity Uptake by the Aerial Roots of Plants

Abstract: Abstract:The mobilization of water by the plant is one of the main challenges of the moment given the threats of food insecurity whose main cause is climate change. The atmosphere contains moisture at any time of the year in the arid or semiarid zone. Apart from the underground roots naturally possessed by many plants, there are plants which possess exclusively or not aerial roots. In the search for methods of adapting crops to water stress, it is imperative to deepen knowledge about interaction between atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The author first showed that the current trend of atmospheric humidity variation in Benin will remain unchanged for the RCP4.5 and RCP8.5 scenarios and will therefore available. Then, he studied the influence of the parameters (coefficient of diffusion of water vapor, duration of the exposure of the velamen to the humidity, the thickness of the velamen, the thickness of the boundary layer, and the temperature of the air surrounding the roots) on the adsorption, entry and migration of water molecules in the velamen [62,63]. He comes to the conclusion that:…”
Section: Recent Studies On Dewmentioning
confidence: 99%
“…The author first showed that the current trend of atmospheric humidity variation in Benin will remain unchanged for the RCP4.5 and RCP8.5 scenarios and will therefore available. Then, he studied the influence of the parameters (coefficient of diffusion of water vapor, duration of the exposure of the velamen to the humidity, the thickness of the velamen, the thickness of the boundary layer, and the temperature of the air surrounding the roots) on the adsorption, entry and migration of water molecules in the velamen [62,63]. He comes to the conclusion that:…”
Section: Recent Studies On Dewmentioning
confidence: 99%